THE ROLE OF THE CONSTITUTIONAL COURT IN RESOLVING ELECTION DISPUTES FROM THE PERSPECTIVE OF JUSTICE - Rosalina Indah Sari; Hendri Hidayat; Ratna Sari (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The authority of the Constitutional Court is regulated in Article 24C(1) of the Constitution. This Court has the authority to adjudicate at the first and final levels, and its decisions are final, with the aim of strengthening the legal system by reinforcing its foundations in the constitution. In this role, the Constitutional Court prevents the existence of laws that are contradictory to the constitution. The Constitutional Court is a judicial institution specifically dealing with constitutional or political justice, which was established after the amendment of the 1945 Constitution of the Republic of Indonesia. Its main purpose is to avoid unilateral decisions in constitutional cases. As the guardian of the constitution, the Judges of the Constitutional Court play an important role in preventing the enactment of laws that violate the constitution. Furthermore, the Constitutional Court also has a role in resolving electoral disputes as a state judicial institution. It decides cases involving disputing parties through judicial processes. The tasks and authorities of the Judges of the Constitutional Court are crucial in assessing electoral disputes. Although this institution receives, examines, and decides criminal cases, the decisions rendered are based on the principles of freedom, honesty, and impartiality in court proceedings, in accordance with the provisions of the law. The Constitutional Court serves as an institution that seeks justice in electoral dispute resolutions. The quality contribution of judges in deciding disputes is vital in achieving justice. Judges must possess professionalism and good morals, as well as legal expertise and a belief in truth. Additionally, the ability to consider the facts of the trial, evidence, witness testimonies, and expert opinions is also an important aspect of assessment. Every decision made by the Judges is based on applicable regulations, thereby strengthening the role of the judicial institution in achieving fair justice. Therefore, high-quality judicial decisions hold the same significance as decisions that reflect justice.